Susceptibility of three indigenous Indonesian fish species: mahseer (Tor soro), snakehead (Channa striata), and bagrid catfish (Hemibagrus nemurus) against parasites infection - Sumiati, Tuti; Taukhid, Taukhid; Andriyanto, Septiyan; Wadjdy, Edy Farid (Journal Omni-Akuatika, 2022)
AbstractÂ Mahseer "dewa" (Tor soro), snakehead "gabus" (Channa striata), and bagrid catfish "baung" (Hemibagrus nemurus) are local specific fish species that are promising to be developed as freshwater aquaculture commodities in Indonesia. Disease cases/outbreaks in those fish farming have often been reported, however, there is not much information on the epizootiology and disease status of those fish species. The susceptibility of those fish to parasitic infection was evaluated by natural and artificial infection. Natural infection was conducted by randomly sampling 20 fish at 5-day intervals and lasting for 30 days. In artificial infection, 150 tested fish cohabited with 40 parasite-carrying fish that were known to be definitely infected by the parasite. The observation was carried out by sampling 20 fish at 5-day intervals and lasting for 30 days. The results showed that the three fish species were susceptible to infection with Trichodina spp, Epistylis spp, Tetrahymena spp, Ichtyophthirius multifiliis, Dactylogyrus spp, and Gyrodactylus spp, while the helminth parasite Pallisentis nagpurensis (Acanthocephala) was only identified in snakehead. A number of parasites such as I. multifiliis, Dactylogyrus spp., and Gyrodactylus spp. are likely to be potential obstacles in the cultivation of those fish species, especially in hatcheries and nurseries.Â Keywords: mahseer, snakehead, bagrid catfish, parasites